THE INFLUENCE OF BOOKLET MEDIA ON KNOWLEDGE AND ATTITUDES ON STRESS FACTORS DURING PREGNANCY - Sophiatunnufus, Octy; Sefrina, Linda Riski (HEARTY, 2024)
Anemia in pregnancy is a condition of pregnant women with significant hemoglobin levels below 12 grams. Anemia of pregnancy can result in various complications that contribute to increased maternal and perinatal morbidity and mortality. The aim of this research is to determine the effect of providing nutritional counseling using booklet media on knowledge and attitudes about stress factors in pregnant women. The sample was anemic pregnant women in the work area of the Pedes Karawang Community Health Center in Payungsari Village and Karangjaya Village, totaling 30 respondents. The intervention is in the form of nutrition education using counseling methods. Knowledge and attitudes were measured using a questionnaire and data analysis using the Wilcoxon Test. The statistical results show that there are significant results between knowledge and attitudes using booklet media with a p.value of 000. The conclusion of this research is that there is an effect of providing nutritional counseling using booklet media on knowledge and attitudes about stress factors in pregnant women.